Measured and predicted frictional pressure drop for boiling zeotropic mixed refrigerants in horizontal tubes. (July 2016) - Barraza, Rodrigo; Nellis, Gregory; Klein, Sanford; Reindl, Douglas
Highlights: Experimental frictional pressure drop data for boiling zeotropic mixtures. Data is collected in horizontal tubes of 0.5 mm and 1.5 mm diameter. Temperature glides include temperatures ranging from 100 K to room temperature. Mass flux, pressure, tube diameter, and mixture composition effects are studied. The Awad and Muzychka (1) correlation shows the best. Abstract: Zeotropic mixtures are widely used in mixed refrigerant Joule–Thomson cryocoolers for various applications such as cryoprobes. Within the Joule–Thomson cycle, multicomponent mixtures exist in a two-phase condition throughout a large portion of the system. Frictional pressure drop correlations for zeotropic refrigerants operating at these conditions are necessary for designers to optimize these systems; however, there are limited experimental data on the two-phase pressure drop of these mixtures available in the open literature. This paper provides experimental data for the frictional pressure drop exhibited by a set of multicomponent zeotropic mixtures boiling in small channels over temperatures ranging from 100 K to room temperature along with the sensitivity of frictional pressure drop to parameters such as mass flux, pressure, tube diameter, and mixture composition. The measured data are compared to several pressure drop correlations available in the literature and the Awad and Muzychka (definition 1) correlation (Awad and Muzychka, 2008) was able to predict the frictional pressure drop over the range of experimental data considered, with an Absolute Average Deviation (AAD) of 17%. The second best correlation is Sun and Mishima (2009) with an AAD of 18%. In addition, the Cicchitti et al. (1959), Müller-Steinhagen and Heck (1986) and Mishima and Hibiki (1996) correlations also show reasonable agreement with the experimental data. Based on our data, the Awad and Muzychka (definition 1) (Awad and Muzychka, 2008) homogeneous model is recommended for prediction of pressure drop because this correlation agrees with 81% of our data with a relative absolute error lower than 25%.